Algunos problemas de la epistolografía griega. ¿Es posible una clasificación epistolar? (Minerva, 2019)
This article treats one of the most important problems seen in the epistolary genre, the establishing of a method of epistolary classification. Given the variety and richness of this genre, it is very difficult to define its many subcategories. This classification attempts to improve defects in previous classifications. It is based on functional criteria, the authenticity of the letter and the intentions of its writer.